Vaccine rhetorics - Lawrence, Heidi Yoston (The Ohio State University Press, 2020)
"Applies rhetorical theory, object-oriented ontology, and theories of materiality to examine the full spectrum of vaccination viewpoints from doctors, patients, and parents and in order to better understand and develop a nuanced model of the vaccination/anti-vaccination debate"--